Surfactant protein A binds TGF-β1 with high affinity and stimulates the TGF-β pathway. Issue 2 (February 2014) - Willems, Coen HMP; Zimmermann, Luc JI; Kloosterboer, Nico; Kramer, Boris W; van Iwaarden, J Freek
We were able to demonstrate reversible, specific and high-affinity binding of radioactively-labelled TGF-β1 ( 125 I-TGF-β1) to immobilized surfactant protein A (SP-A), with an apparent dissociation constant of 53 picomolar at ∼21℃. Addition of a 200-fold molar excess of the latency associated peptide (LAP) prevented and dissociated the binding of 125 I-TGF-β1 to SP-A, whereas latent TGF-β1 had no effect. Using a bioassay for TGF-β1 activity—a luciferase reporter assay—we were able to show that SP-A in the presence of TGF-β1 stimulated the TGF-β1 pathway, whereas SP-A alone had no effect. Studies with structural analogues of the distinct SP-A tail domain and head domain indicated that stimulatory activity of SP-A resided in the head domain. No activation of latent TGF-β1 by SP-A was observed. In addition, we observed that SP-A inhibited TGF-β1 inactivation by LAP. These results indicate that SP-A may have a regulatory role in the TGF-β1-mediated processes in the lung.